The Effect of Arrowroot Flour (Maranta Arrundinaceae) on Physical And Sensoric Qualitiy of Rabbit Nugget - Ulfi Noor Hakim; Djalal Rosyidi; Aris Sri Widati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2013)
This experiment was conducted to observe the effect of addition level of arrowroot flour (Maranta arrundinaceae) on physical and sensoric quality of rabbit nugget. Rabbit meat and arrowroot flour were used in current experiment. There were four treatments with three repetations in current experiment, addition level of arrowroot flour 0 % (P0), 10 % (P1), 20 % (P2), and 30 % (P3) in rabbit nugget. The variables measured in experiment were physical quality (pH, water holding capacity, and texture) and sensory quality (color, flavor, odour, and texture). This experiment was statisically analyzed by using Completelly Randomized Design (CRD). The difference between means was analyzed by Duncan’s Multiple Range Test (DMRT). This experiment showed that pH, water holding capacity, and sensoric quality (color, flavor, odour, and texture) were significantly affected (P < 0.01) by the addition of arrowroot flour, while it did not significanlty affect (P > 0.05) in physical texture. The addition level 20 % of arrowroot flour (P2) gave the highest value on physyical and organoleptic quality of rabbit nugget. The conclusion of this experiment was the increase of addition level of arrowroot flour in rabbit nugget improved the phyical texture, but it reduced pH, water holding capacity, and sensoric palatability (color, flavor, odour, and texture).